Factors associated with health-related quality of life among patients with liver cirrhosis in Egypt. Issue 1 (March 2015) - Youssef, Naglaa F.A.; Shepherd, Ashley; Evans, Josie M.M.
<x xml:space="preserve">Abstract</x> Background Although the disease burden of liver cirrhosis in Egypt is high and there are few resources for its management, there is limited research on the health-related quality of life (HRQOL) of Egyptian patients with liver cirrhosis. Aims To describe the HRQOL of liver cirrhotic patients in Egypt and to analyse factors associated with this construct. Patients and methods A cross-sectional study with a convenience sample of 401 patients from three hospitals in Cairo, Egypt, was carried out in June–August 2011. Patients were interviewed to complete a background data form, Short Form-36, the Liver Disease Symptom Index-2.0 and the Multidimensional Scale of Perceived Social Support. Results Patients had low HRQOL, with mental health perceived to be poorer than physical health. In regression analyses, severity of symptoms, disease stage, comorbidities and employment status were associated significantly with physical health, accounting for 19% of the variance. For mental health, 31.7% of the variation was explained by severity of symptoms, employment status and perceived spouse and family support. Conclusion and recommendations These findings highlight the needs of patients with liver cirrhosis in Egypt. Engaging the patients' family in care planning may decrease patients' burden and improve their HRQOL. This study also provides a rationale to develop future research in symptom management to enhance HRQOL.